The intention to purchase imitation apparels among Generation Y / Muhammad Zahirul Hakim Abd Aziz - Abd Aziz, Muhammad Zahirul Hakim (Faculty of Business and Management, 2018)
The purpose of this study was to to identify the factor that causes the intention to purchase imitation apparels among Generation Y. The dependent variable in this research is the intention to purchase imitation apparel which is measured by independent variables such attitudes, perceived behavioral control, subjective norm, economic benefit and hedonic benefit as well. The respondents were consumers from Generation Y who are ages between 18 to 35 years old, who have experienced in purchasing imitations. Therefore, 140 questionnaires were being collected and used in this study. The finding showed that attitudes, perceived behavioral control, subjective norm, economic benefit and hedonic benefit, have influence on the intention to purchase imitations apparels among Generation Y. All variables show significance relationship towards the factor to purchase imitations apparels. Meanwhile, the researcher apply questionnaire as the process to gather all the data from sample respondents in accomplish the research objectives. To analyze the data, descriptive analysis, reliability test, correlation analysis and standard coefficient were used. The result of the study presented in this research agreed that attitudes, perceived behavioral control, subjective norm, economic benefit and hedonic benefit, can influence the intention to purchase imitations apparels among Generation Y.